Innocent until proven guilty: suspicion of deception in online reviews. (15th April 2022) - Petrescu, Maria; Kitchen, Philip; Dobre, Costinel; Ben Mrad, Selima; Milovan-Ciuta, Anca; Goldring, Deborah; Fiedler, Anne
Abstract : Purpose: This study aims to formulate a new framework for identifying deception in consumer reviews through the lens of interpersonal deception theory (IDT) and the persuasion knowledge model (PKM). It evaluates variables contributing to consumer intentions to purchase after reading deceptive reviews and proposes deception identification cues to be incorporated into the interpersonal communication theoretical framework. Design/methodology/approach: The first study is qualitative and quantitative, based on sentiment and lexical analysis of 1, 000 consumer reviews. The second study uses the US national consumer survey with a partial least squares partial least squares-structural equation modeling and a process-based mediation–moderation analysis. Findings: This study shows deceptive characteristics that cannot be dissimulated by reviewing consumers that represent review legitimacy based on review valence, authenticity, formalism and analytical writing. The results also support the central role of consumer suspicion of an ulterior motive, with a direct and mediation effect regarding consumer emotions and intentions, including brand trust and purchase intentions. Research limitations/implications: This paper presents a new framework for identifying deception in consumer reviews based on IDT and PKM, adding new theoretical elements that help adapt these theories to written digital communication specificities. This study clarifies the role of suspicion in a deceptive communication context and shows the variables contributing to consumers' purchase intention after reading deceptive reviews. The results also emphasize the benefits of lexical analysis in identifying deceptive characteristics of reviews. Practical implications: Companies can consider the vulnerability of certain generations based on lower levels of suspicions and different linguistic cues to detect deception in reviews. Long-term, marketers can also implement deception identification practices as potential new business models and opportunities. Social implications: Policymakers and regulators need to consider critical deception cues and the differences in suspicion levels among segments of consumers in the formulation of preventative and deception management measures. Originality/value: This study contributes to the literature by formulating a new framework for identifying deception in consumer reviews, adapted to the characteristics of written digital communication. This study emphasizes deception cues in electronic word-of-mouth and provides additional opportunities for theorizing deception in electronic communication.